Synthesis of BIS (2-methylcylopropyl) methanone from y-valerolactone - Nur Nazrina Ahmad Sabri, 1989-; Khatijah Zakariah, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2010